Executive businesswomen's learning in the context of organizational culture. - Laura L. Bierema (Adult Education Research Conference, 1997)
Case study analysis was used to investigate executive women's learning and development in corporate culture. Eleven executives were interviewed. A model of their development is proposed, detailing their learning tactics, negotiation strategies and transition characteristics over the course of their career development.